2008
DOI: 10.1152/ajpregu.00164.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lower uterine artery blood flow and higher endothelin relative to nitric oxide metabolite levels are associated with reductions in birth weight at high altitude

Abstract: Moore LG. Lower uterine artery blood flow and higher endothelin relative to nitric oxide metabolite levels are associated with reductions in birth weight at high altitude. Am J Physiol Regul Integr Comp Physiol 295: R906 -R915, 2008. First published June 25, 2008 doi:10.1152/ajpregu.00164.2008.-Reduced uteroplacental blood flow is hypothesized to play a key role in altitude-associated fetal growth restriction. It is unknown whether reduced blood flow is a cause or consequence of reduced fetal size. We asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 36 publications
7
108
0
1
Order By: Relevance
“…Hospital-based studies have documented that the risk of adverse perinatal outcomes is increased with extreme maternal Hcts (Moore et al, 2001a;Gonzales et al, 2009) (Fig.4). During pregnancy at high altitude, elevated Hct and the associated increase in blood viscosity contribute to an increased risk of stillbirth, preterm birth, and reduced birth weight, all of which appear to stem from a reduced uterine artery blood flow and, consequently, a reduced rate of O 2 delivery to the uteroplacental circulation (Moore et al, 1982;Moore et al, 2001a;Moore et al, 2001b;Zamudio et al, 1995;Wilson et al, 2007;Julian et al, 2008;Julian et al, 2009b). For this reason, acclimatized lowlanders at high altitude generally experience especially high rates of adverse pregnancy outcomes.…”
Section: Erythropoeitic Activitymentioning
confidence: 99%
“…Hospital-based studies have documented that the risk of adverse perinatal outcomes is increased with extreme maternal Hcts (Moore et al, 2001a;Gonzales et al, 2009) (Fig.4). During pregnancy at high altitude, elevated Hct and the associated increase in blood viscosity contribute to an increased risk of stillbirth, preterm birth, and reduced birth weight, all of which appear to stem from a reduced uterine artery blood flow and, consequently, a reduced rate of O 2 delivery to the uteroplacental circulation (Moore et al, 1982;Moore et al, 2001a;Moore et al, 2001b;Zamudio et al, 1995;Wilson et al, 2007;Julian et al, 2008;Julian et al, 2009b). For this reason, acclimatized lowlanders at high altitude generally experience especially high rates of adverse pregnancy outcomes.…”
Section: Erythropoeitic Activitymentioning
confidence: 99%
“…Xiao et al suggested that high altitude hypoxia altered uterine vessels myogenic activity via enhanced oxidative stress (34). Residence at high altitude per se was reported to induce significant elevation of several vasoconstriction relative to vasodilatation mediators (3,18). This effect is apparently more pronounced during pregnancy, with greater levels of certain vasoconstrictor, inhibition of other vasodilator mediators, compared with low-altitude pregnancy.…”
mentioning
confidence: 99%
“…They found a lowered birth weight at a high altitude than at a moderate altitude, but they reported no significant differences in the Doppler indices of the umbilical and mid-cerebral arteries. Julian et al (13) found no differences at any time in the umbilical or mid-cerebral arteries Doppler flow parameters at low altitude than high altitude. Indeed, the fetus of pregnant sheep acclimatized to long-term hypoxia had similar increases in the cerebral blood flow and cerebral tissue oxygenation to the fetus at a low altitude (26).…”
Section: Discussionmentioning
confidence: 91%
“…Kumtepe et al (8) demonstrated a greater incidence of eclampsia among women living at high altitudes (>1500 m). There are studies in the literature comparing the effect of altitude on maternal and fetal Doppler flow parameters; however, these studies have conflicting results (9)(10)(11)(12)(13)(14)(15). For instance, Galan et al (14) reported no uteroplacental or fetal vascular Doppler velocimetry differences between moderate highlanders and lowlanders, whereas Krampl et al (11) reported a lower impedance of uterine artery blood flow in women living at a high altitude than at the sea level.…”
Section: Introductionmentioning
confidence: 99%